KAJIAN TEKNOLOGI PEMANFAATAN BIOGAS POME (PALM OIL MILL EFFLUENT) KE BOILER - Sucahyo, Bambang; H, Dwi Lukman; Ridlo, Rohmadi; R, Tyas Puspita; S, Erna Rosmala (Majalah Ilmiah Pengkajian Industri, 2019)
In collaboration with BPPT,  PTPN V management starting in 2018 took place at the Sei Pagar  Mill PTPN V in Riau Province, planning the implementation of Biogas to Boiler technology to maximize the use of Biogas. The study aims to substitute shells for steam boilers / kettle through the scheme of using biomass POME to boilers at palm oil mills. The Utilization Model is a simple representation  of a complex process in reality. To produce the scheme the model was preceded by conducting technical studies and economic studies and comparative studies on several Mill s in Sumatra and Kalimantan. From some of the findings from the studies that were compiled, one of the most suitable models will be made that will be applied in the Sei Pagar Mill. Furthermore, from the model, still through the RISTEKDIKTI Flagship Insinas Program, it will be developed to produce Prototypes and Construction / modifications to the Existing Boiler that is applied to the Sei Pagar Mill . Utilization Model Scheme. Biogas POME to Boilers at Palm Oil Mill by applying Biogas to Boiler technology includes several components of equipment, such as: Blower, Piping System, Valve Train, Gas Burner (Single Burner), Forced Draft Fan, and Control Panel (PHB). Utilization Model. Biogas POME to Boilers at Palm Oil Mill can later be developed and implemented to support the application of Biogas to Boiler technology at Palm Oil Mills in Indonesia.Keywords: Steam Boiler / Boiler, Blower, Piping System, Valve Train, Gas Burner (Single Burner), Forced Draft Fan, and Control Panel (PHB)